Review of Homalocnemidae of Chile with a key to species and descriptions of male and female terminalia (Diptera: Empidoidea) - Rafael, José A.; Marques, Dayse W.a.; González, Christian R.; Sinclair, Bradley J. (Zootaxa, 2022)
The Homalocnemidae of Chile is reviewed, including the descriptions of the male and female terminalia of the two known species: H. nigripennis Philippi and H. praesumpta Collin. All references pertaining to Chilean Homalocnemis Philippi and the two known species are provided. Geographical distributions of the species were compiled and mapped from bibliographic data and collections. An illustrated key to the two species is also presented.